The Role of Expression Card Media in Supporting Emotion Recognition in Late Adolescents with Intellectual Disabilities - Oktantri, Devi Dwi; Megawasearie, Rosika; Sugihartatik (Indonesian Journal of Instructional Media and Model, 2025)
The ability to recognize and express emotions is often a critical issue that hinders social participation and quality of life among young people with intellectual disabilities (IDs). The purpose of this study was to examine the role of expression cards in supporting emotional recognition in late adolescents, focusing on the effectiveness of the intervention and participants' perceptions of use. Design This was a single-group quasi-experimental, test-retest study to investigate the effectiveness of expression cards in improving emotion recognition in late adolescents with mild to moderate intellectual disabilities. A total of 35 participants aged 16 to 21 years old. Quantitative data were analyzed using paired sample t-tests to compare pretest and posttest scores, while ANCOVA was used to control for potential covariates such as age, gender, and baseline cognitive function. The use of expression cards significantly improved emotion recognition skills in late adolescents with mild to moderate intellectual disabilities. From an emotional developmental perspective, the use of expression cards supports the stages of affective development by providing a visual aid that helps individuals recognize and express emotions more effectively